Cut-off value to identify a flare using the Flare Assessment in Rheumatoid Arthritis (FLARE-RA) questionnaire: analysis of the TOSCA study. (31st March 2021) - Aouad, Krystel; Gaudin, Philippe; Vittecoq, Olivier; Morel, Jacques; Berthelot, Jean-Marie; Senbel, Eric; Schaeverbeke, Thierry; Lioté, Frédéric; Flipo, René-Marc; Pinta, Alexandrine; Guillemin, Francis; Fautrel, Bruno
Abstract: Objective: The Flare Assessment in RA (FLARE-RA) self-administered questionnaire aims to identify patients who had flare in the interval between two consultations. This study aimed to establish a threshold for FLARE-RA score to identify RA flare. Methods: The Tocilizumab SubCutAneous study evaluated the efficacy and safety of s.c. tocilizumab (TCZ) to patients with active RA. Disease activity was assessed with the DAS28ESR at baseline and at week 2 (W2), W4, W12 and W24. The FLARE-RA questionnaire was administered at W12 and W24. Patient satisfaction, assessed at baseline and W24 with the Patient Acceptable Symptom State (PASS), was used as a surrogate marker of no flare. A correlation was sought between the FLARE-RA score at W12 and W24 and the area under the receiver operating characteristic (ROC) curve (AUC) for monthly DAS28ESR . The optimal FLARE-RA cut-off below which patient satisfaction reached the PASS was explored with an ROC curve. Results: A total of 139 patients were included (mean age 57.3 ± 13.8 years, 74.1% women, mean RA duration 10.8 ± 9.2 years, mean DAS28ESR 5.8 ± 1.1). The correlation between the FLARE-RA score and DAS28ESR AUC was moderate at all times: ρ = 0.41 at W12 ( P  < 0.0001) and 0.51 at W24 ( P  < 0.0001). The optimal cut-off for the FLARE-RA score to identify absence of flare (i.e. an acceptable situation based on the PASS) was 2.3 with an AUC of 0.81. Conclusion: FLARE-RA and DAS28ESR assessment differ; we propose a FLARE-RA cut-off of 2.3, below which the situation (i.e. without flare) is acceptable for patients.